AEC 2015 challenges affecting labor mobility and MRAS on professional services - Aldaba, Rafaelita M. (Philippine Journal of Development, 2012)
The paper aims to identify the facilitating and deterring factors affecting the implementation of the ASEAN mutual recognition arrangements (MRAs) in professional services encompassing engineering, nursing, architecture, surveying, medical, dental practice, and accountancy. Overall, the progress of MRA implementation in the Philippines has been slow. For all professions, the issue of enacting new rules and/or regulations has been difficult due to constitutional and other restrictions. Clear procedures and guidelines should be formulated for the implementation of the reciprocity provision. For temporary special permits, the law needs to be revised to allow complete borderless practice.